PENGARUH KONSTANTA LAJU TRANSPORT ORGAN PANKREAS PADA PENCAPAIAN KONSENTRASI GLUKOSA DARAH NORMAL DENGAN PEMODELAN - Asra, Azmi (Edu Research, 2012)
Through the study replica regulatory process glucose and insulin concentrations in the body, it has studied the influence of parameter mechanisms of pancreatic organ transport rate constant (Kï¢) on achieving normal levels of glucose concentration. In this study has been carried out curve fitting method between clinical data and model equations glucose and insulin concentrations for the three conditions of the patient, namely: glucose low, normal and high of six patients.